Activation of canonical Wnt/β‐catenin signaling stimulates proliferation in neuromasts in the zebrafish posterior lateral line. Issue 7 (5th June 2013) - Head, Jeffery R.; Gacioch, Leah; Pennisi, Matthew; Meyers, Jason R.
<x xml:space="preserve">Abstract</x> Background: The posterior lateral line in zebrafish develops from a migrating primordium that deposits clusters of cells that differentiate into neuromasts at regular intervals along the trunk. The deposition of these neuromasts is known to be coordinated by Wnt and FGF signals that control the proliferation, migration, and organization of the primordium. However, little is known about the control of proliferation in the neuromasts following their deposition. Results: We show that pharmacological activation of the Wnt/β‐catenin signaling pathway with 1‐azakenpaullone upregulates proliferation in neuromasts post‐deposition. This results in increased size of the neuromasts and overproduction of sensory hair cells. We also show that activation of Wnt signaling returns already quiescent supporting cells to a proliferative state in mature neuromasts. Additionally, activation of Wnt signaling increases the number of supporting cells that return to the cell cycle in response to hair cell damage and the number of regenerated hair cells. Finally, we show that inhibition of Wnt signaling by overexpression of dkk1b suppresses proliferation during both differentiation and regeneration. Conclusions: These data suggest that Wnt/β‐catenin signaling is both necessary and sufficient for the control of proliferation of lateral line progenitors during development, ongoing growth of the neuromasts, and hair cell regeneration. Developmental Dynamics 242:832–846, 2013. © 2013 Wiley Periodicals, Inc.